-5z-5=-2z+10

Simple and best practice solution for -5z-5=-2z+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5z-5=-2z+10 equation:


Simplifying
-5z + -5 = -2z + 10

Reorder the terms:
-5 + -5z = -2z + 10

Reorder the terms:
-5 + -5z = 10 + -2z

Solving
-5 + -5z = 10 + -2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '2z' to each side of the equation.
-5 + -5z + 2z = 10 + -2z + 2z

Combine like terms: -5z + 2z = -3z
-5 + -3z = 10 + -2z + 2z

Combine like terms: -2z + 2z = 0
-5 + -3z = 10 + 0
-5 + -3z = 10

Add '5' to each side of the equation.
-5 + 5 + -3z = 10 + 5

Combine like terms: -5 + 5 = 0
0 + -3z = 10 + 5
-3z = 10 + 5

Combine like terms: 10 + 5 = 15
-3z = 15

Divide each side by '-3'.
z = -5

Simplifying
z = -5

See similar equations:

| 2(6)+3(-4)-(-2)=2 | | 15-11=2(x-8) | | 6(y-1)=5y+4 | | 20x+4=6x+4 | | -4(y+1)=0 | | 20x+4=8x+18 | | 4x^2-12x+9=equation | | 2/3x-5/3x | | 4(y+3)=2y+20 | | 3(6)-3(-4)+10(-2)=10 | | 30=5d-3d | | -2.24n=-12.168 | | x-12=x/10 | | 7x-1=8x+2 | | X-3-3x=3(1+x) | | y^4+12y^2+36=0 | | n/-15=5.3 | | 5(2x+6)=55 | | 1.6=4y+20.4 | | 2cos(x)-3x=0 | | 3x+4=9.5 | | n/14.3=-5 | | -0.166666666667= | | 0.5(y+8)=2(y-1) | | 7+8q=7q | | H=-16t^2+24t+40 | | -2x-1=2x+15 | | n/-12.168=-2 | | z+iz+1=0 | | 12(n+8)=132 | | 10(x+3)-9x-4=x-5+3 | | 4x-15=7x-60 |

Equations solver categories